Pre Clinical- Basic Sciences Teaching Curriculum of a Medical School in a Developing Country -Are We Doing it Right? - Atukorala, Kushani Rasangika; Atapattu, Piyusha (Journal of Bangladesh Society of Physiologist, 2015)
Background: Preclinical teaching of basic sciences provides the basis for the development of clinical reasoning skills and the ability to make management decisions. However, many senior undergraduates, pre-interns and doctors indicate that basic sciences knowledge is poorly recalled and has little relevance to their clinical practice. Objectives: To explore the perceptions of medical students in their clinical years, and pre-interns about the basic sciences courses taught to them in the preclinical years, and to assess how each group rates the applicability of these courses to current clinical training. Methods: A descriptive cross-sectional study was conducted among 118 pre-interns and 146 undergraduate medical students using a self-administered questionnaire, regarding their perceptions on preclinical basic sciences teaching. For statistical analysis chi square test was applied. Results: More than 75% both pre-interns and undergraduates agreed that preclinical teaching was useful and relevant for future clinical work. 50-75% frequently revisited preclinical subjects despite unapparent clinical significance. 55% couldnt remember most of preclinical content. Physiology was the most retained (76%) and most clinically relevant subject (80%). Majority of (>60%) both the groups suggested more teaching time and >75% suggested concurrent clinical exposure for preclinical teaching. Undergraduates and preinterns differed in that 56% of undergraduates and 37% of pre-interns had studied pre clinical subjects just to pass examinations (p<0.01) Conclusions: Majority of undergraduates and pre-interns felt that preclinical teaching is interesting and relevant for future clinical practice, though recall and clinical significance were suboptimal. Revising teaching methods with interdisciplinary integration, early clinical exposure showing relevance of basic sciences and allocating more teaching time utilizing clinicians should be considered. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22806 Bangladesh Soc Physiol. 2014, December; 9(2): 98-104